The use of learning objects for teaching computer programming - Begosso, Luiz Carlos; Begosso, Luiz Ricardo; Ribeiro, Alexandre; Martins dos Santos, Rafaela; Begosso, Raissa Helena (Frontiers in Education 2015 : launching a new vision in engineering education : proceedings : October 21-24, 2015, Camino Real Hotel & Conference Center, El Paso, Texas, 2015)
Information technology has been contributing to various areas of knowledge; in particular, the field of education stands out. In what concerns the teaching of computer programming, literature contains important efforts that aim to assist in the learning process. Teaching algorithms and programming concepts for first year students has always been a great challenge for universities, new Computer Science students usually have difficulties in understanding and abstracting the problem logics. An alternative that has contributed to the teaching-learning process is the use of Learning Objects (LO), which contribute towards mediating and enhancing the teaching-learning process. One of the great difficulties of learning during the initial semesters of Engineering and Computer Science courses is related to the contents of computer programming, which increases the students' failure level and also the dropout rate of such courses. In order to decrease those rates, we have developed a project to create various learning objects to help teach concepts that are considered difficult to understand by students of Science courses, and the results were very positive. This paper presents the qualitative and quantitative results of the experiment we conducted with the development and application of learning objects to help teaching students of Computer Science. The project was conducted in 2013 and 2014 and outcome data showed that the use of learning objects contributes significantly to the teaching-learning process.